Immunological evaluation of HIV-negative invasive fungal disease at Groote Schuur Hospital, Cape Town, South Africa - Onyango, Vonwicks Czelestakov (Department of Medicine, 2020)
Background The majority of invasive fungal disease in South African hospitals is HIV-related or associated with another secondary immunodeficiency e.g. haematopoietic stem cell transplant. After excluding secondary immunodeficiency, a detailed immune work-up can lead to a diagnosis of primary immunodeficiency. Objective To detail an appropriate step-wise immunological work-up for a series of patients with invasive fungal diseases and possible underlying primary immune deficiency. Methods Detailed review of all culture- or histologically confirmed cases of invasive fungal disease (IFD) at Groote Schuur Hospital between 2007-2017. Step-wise immunological work-up of IFD patients with no secondary immunodeficiency. Clinical characteristics and step-wise immunological profiles were evaluated. Results Sixty-seven adults with IFD were identified; 72% (48/67) were HIV-related. 8/19 HIVnegative cases were either deceased (4) or lost-to-follow-up (4). Work-up of the remaining 11 cases found five with non-HIV secondary immunodeficiencies (Lupus, liver transplant, endstage renal failure and haematological malignancy). A primary immunodeficiency was suspected in six cases, but 1 case of cutaneous sporotrichosis was excluded; with five cases (4 with disseminated Cryptococcus neoformans and 1 with cerebral aspergillosis) undergoing detailed immune work-up. A case of idiopathic CD4 lymphopenia was diagnosed; but all other cases had no evidence of neutrophil or a cell-mediated immune defect; including investigations of naïve and memory T-cell subsets and cytokine responses to PHA and candida. All cases were noted to have low baseline vaccine responses and Vitamin D deficiency. Conclusion Invasive fungal disease is predominantly associated with HIV and secondary immunodeficiency in South Africa. Known primary immunodeficiencies can be identified with basic immune work-up; but no obvious functional immune defect is evident in the majority of these cases.